2017
DOI: 10.3390/life7020019
|View full text |Cite
|
Sign up to set email alerts
|

Small and Random Peptides: An Unexplored Reservoir of Potentially Functional Primitive Organocatalysts. The Case of Seryl-Histidine

Abstract: Catalysis is an essential feature of living systems biochemistry, and probably, it played a key role in primordial times, helping to produce more complex molecules from simple ones. However, enzymes, the biocatalysts par excellence, were not available in such an ancient context, and so, instead, small molecule catalysis (organocatalysis) may have occurred. The best candidates for the role of primitive organocatalysts are amino acids and short random peptides, which are believed to have been available in an ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 136 publications
(184 reference statements)
0
34
0
Order By: Relevance
“…In an example, the dipeptide catalyst seryl-histidine has been shown to catalyse the formation of a covalent peptide bond, generating another dipeptide [ 182 ]. This peptide exemplifies the general phenomenon of catalytic small peptides [ 199 ]. Thus, the lipid derivative in which seryl-histidine is a headgroup, linked to any appropriate hydrocarbon tail, would also likely serve as an effective catalyst, perhaps even better than the soluble version, due to facilitated proximity and reduced dimensionality.…”
Section: Lipid Worldmentioning
confidence: 99%
“…In an example, the dipeptide catalyst seryl-histidine has been shown to catalyse the formation of a covalent peptide bond, generating another dipeptide [ 182 ]. This peptide exemplifies the general phenomenon of catalytic small peptides [ 199 ]. Thus, the lipid derivative in which seryl-histidine is a headgroup, linked to any appropriate hydrocarbon tail, would also likely serve as an effective catalyst, perhaps even better than the soluble version, due to facilitated proximity and reduced dimensionality.…”
Section: Lipid Worldmentioning
confidence: 99%
“…Enzymatic hydrolysis with the aid of proteases, such as papain, neutrase, flavorzyme, thermolysin, alcalase, pronase, and ficin, is the most reliable and effective method for producing peptides with functional properties as compared with microbial fermentation and hydrolysis by either acid or alkali (Najafian & Babji, ). Protein degradation that leads to peptides with increased charge density contributes to increased solubility (Wieczorek, Adamala, Gasperi, Polticelli, & Stano, ). Peptides with different biological activities have been recently produced from fish proteins, including seabass (Sae‐leaw et al., ; Sae‐Leaw et al., ), kilka (Zamani, Madani, Rezaei, & Benjakul, ), tilapia (Yarnpakdee, Benjakul, Kristinsson, & Kishimura, ), yellow stripe trevally (Klompong, Benjakul, Kantachote, & Shahidi, ), and sardine (Bougatef et al., ), by enzymatic hydrolysis.…”
Section: Bioactive Peptidesmentioning
confidence: 99%
“…Histidyl-histidine (His-His) catalyzes the dephosphorylation of deoxyribonucleoside monophosphate, the hydrolysis of oligo (A) 12 , and the oligomerization of 2',3'-cAMP under cyclic wet-dry reaction conditions [ 25 ]. More recent studies have shown that seryl-histidine (Ser-His) catalyzes the oligomerization of trimers of imidazole-activated nucleotides [ 26 , 27 ], and catalyze peptide bond formation between two amino acids, an activity also found in seryl-histidyl-glycine (Ser-His-Gly) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%